The algorithm of the electric stimulator VEB-1 software operation - V. Babelyuk; Yu. Dobrovolsky; I. Korsuns'kyi; V. Kuzenko; I. Popovych; W. Zukow (Kazimierz Wielki University, 2020)
This thesis demonstrates results of the electric stimulator VEB-1 software operation algorithm development. To increase the device efficiency, the algorithm is composed using the frequency beat method. Our software solutions allowed us to provide the needed precision to maintain the operating frequency of the electric current pulses that penetrate through the human body on the level not less than 0,001Hz. The software allows the operator to control the electrostimulation process through the screen, where all active processes are displayed.